Downregulation of epithelial apoptosis and barrier repair in active Crohn's disease by tumour necrosis factor α antibody treatment. Issue 9 (11th August 2004) - Zeissig, S; Bojarski, C; Buergel, N; Mankertz, J; Zeitz, M; Fromm, M; Schulzke, J D
Abstract : Background and aims: Barrier dysfunction is an important feature contributing to inflammation and diarrhoea in Crohn's disease (CD). Recently, tumour necrosis factor α (TNF-α) antibodies were recognised as effective in steroid refractory CD. The aim of this study was to characterise the effects of this therapy on the epithelial barrier. Patients and methods: Forceps biopsies were obtained from the sigmoid colon before and 14 days after TNF-α antibody therapy in 11 patients treated for chronic active CD (Crohn's disease activity index >150). Epithelial apoptoses were measured after terminal deoxynucleotidyl transferase mediated deoxyuridine triphosphate nick end labelling (TUNEL) and 4′, 6-diamidino-2-phenylindole staining. Epithelial resistance was determined by alternating current impedance analysis in miniaturised Ussing chambers. Occludin, claudin 1, and claudin 4 expression was quantified in immunoblots. Results: The epithelial apoptotic ratio was 2.1 (0.2)% in controls and increased to 5.3 (1.0)% in CD. TNF-α antibody therapy decreased the apoptotic ratio to 2.9 (1.0)% (normalised in 10 of 11 patients). In parallel, epithelial resistance was lower in CD than in controls (24 (3) v 42 (3) Ω×cm 2 ) and improved to 34 (3) Ω×cm 2 after therapy. Occludin, claudin 1, and claudin 4 were not affected by TNF-α antibody therapy. In support of a functional role of epithelial apoptoses in CD, a similar decrease in resistance of −40% was observed when the apoptotic rate was selectively upregulated from 2.6% to 5.4% with camptothecin in HT-29/B6 cells. Conclusions: Epithelial apoptoses were upregulated in the colon in CD and restored to normal in 10 of 11 patients by TNF-α antibody therapy. This is the structural correlate of epithelial barrier dysfunction measured as epithelial resistance while expression of tight junction proteins did not contribute to this therapeutic effect.